Benign multicystic peritoneal mesothelioma: a case report (Journal of Pathology of Nepal, 2021)
Free-floating peritoneal masses found during laparotomy should arouse a suspicion of benign multicystic peritoneal mesothelioma and they must be removed and subjected to histopathological examination and immunochemical staining to ascertain their benign nature. The objective of the study was to report a rare case of benign multicystic peritoneal mesotheliomas. We report an incidental finding of multiple free-floating peritoneal masses in a pregnant primigravida woman with a normal antenatal course who underwent a cesarean section in a rural hospital setting in India for fetal distress. The masses were removed from the peritoneal cavity during the surgery and subjected to histopathological examination and found to be benign multicystic peritoneal mesotheliomas. Immunohistochemistry of the cysts revealed that the mesothelial cells lining the cysts were positive for calretinin and WT1 and negative for CD31.